The remarkable outflows from the galactic microquasar SS433 - Jeffrey, R (2016)
In this thesis, I present 4 new, high-resolution observations of the Galactic microquasar SS 433, obtained from the Very Long Baseline Array (VLBA). I show that we can resolve the same ejecta in successive observations separated by ∼ 35 d. I will demonstrate a method to uniquely determine launch vectors of the jet bolides, and I use this unprecedented baseline in time to show that the expansion rate of these bolides may reach 0.03c. I also present the first scientific results from the study of the radio jets in a unique set of historic observations of SS 433: the 39 images that comprise the 2003 VLBA movie of Mioduszewski et al. (2004). This unmatched time sampling allows us to see daily changes in the dynamics of SS 433's jets. I present evidence that these observations caught SS 433 as it transitioned from quiescence into a flare, and I show that this manifests itself as an increase in both the jet launch speed and the brightness of the jet bolides. Using these data, I examine the evolution of the particle energies, densities and magnetic fields within the bolides. We see that the estimates of the mass-loss rates via the jets cannot be reconciled with the those inferred from X-ray or optical data, if we posit equipartition of energy in synchrotron emitting plasma. The time resolution of the 2003 data allows us to observe the flux evolution of the jet bolides, and I show that the bolides undergo a power law decay as t−2.8. Lastly, I examine X-ray monitoring data from the Swift/BAT satellite and the MAXI All-Sky- Monitor. From these lightcurves, I examine the geometry of the X-ray emission from close to the compact object itself, and I discuss SS 433’s place within the current paradigm of accretion in microquasars. Throughout, we will see that it is the accessible time scales of the SS 433 phenomenon that allow us to learn about its exciting, complex physics.